Living livestock research: Towards policies for people and pigs in Northeast India - Ficarelli, P.P. (International Livestock Research Institute, 2011)
In this short video 'towards policies for people and pigs in Northeast India,' we report from Umlathu where we explore with villagers the multiple realities of livestock farming. The focus is on pig farming and on local perspectives and demands for its development. This video reports from a project 'Better livelihoods through improvement of livestock production and marketing in North East India' which is funded by IFAD as part of a larger project 'Livelihood improvement and empowerment of rural poor through sustainable farming systems in North East India' funded by the World Bank and Government of India.